Assesment of Enviromentally Friendly Transportation to Achieve Sustainable Transportation in Semarang City - Firdaus, Aditya Zulfikar; Kurniati, Rina (Universitas Ibn Khaldun Bogor, 2025)
Transportation is the main infrastructure that has a role in driving the economy. The transportation sector can also be a problem if mobility is not accompanied by the availability of adequate infrastructure. Semarang City has the highest number of vehicles compared to other cities or regencies in Central Java Province. Based on data from BPS Semarang City, the number of motorized vehicles in Semarang City in 2021 reached 1,875,781 vehicles with the growth of motorized vehicles increasing by 12% every year. The high number of motorized vehicles in Semarang City causes congestion, air pollution and increases fuel consumption. Semarang City has started to initiate and design an environmentally friendly transportation system that leads to green transportation. The concept of green transportation is an environmentally friendly and sustainable transportation that aims to reduce vehicle emissions and create road space for pedestrians and bicycles. This is in line with the mission of Semarang City in realizing quality infrastructure that is environmentally sound and sustainable. The purpose of this study is to examine the implementation of green transportation that has been carried out in Semarang City in achieving sustainable transportation. This research uses a qualitative approach, This research uses a qualitative approach, while the analysis is carried out by descriptive analysis as well as scoring and weighting analysis so as to obtain the results of the value of the application of environmentally friendly transportation that leads to the concept of green transportation. The results obtained show that Semarang City in implementing environmentally friendly transportation that leads to green transportation has been quite good or quite successful.